Lithium promotes long-term neurological recovery after spinal cord injury in mice by enhancing neuronal survival, gray and white matter remodeling, and long-distance axonal regeneration - Balçıkanlı, Zeynep; Culha, Irem; Dilsiz, Pelin; Aydin, Mehmet Serif; Ates, Nilay; Beker, Mustafa Caglar; Baltaci, Saltuk Bugra; Koc, Halil I.; Yigitbasi, Ahmet; Gündogar, Mustafa; Doeppner, Thorsten R.; Hermann, Dirk M.; et al. (Frontiers in Cellular Neuroscience, 2022)
Spinal cord injury induces neurological deficits associated with long-term functional impairments. Since the current treatments remain ineffective, novel therapeutic options are needed. Besides its effect on bipolar mood disorder, lithium was reported to have neuroprotective activity in different neurodegenerative conditions, including spinal cord injury. In spinal cord injury, the effects of lithium on long-term neurological recovery and neuroplasticity have not been assessed. We herein investigated the effects of intraperitoneally administered lithium chloride on motor coordination recovery, electromyography (EMG) responses, histopathological injury and remodeling, and axonal plasticity in mice exposed to spinal cord transection. At a dose of 0.2, but not 2.0 mmol/kg, lithium chloride enhanced motor coordination and locomotor activity starting at 28 days post-injury (dpi), as assessed by a set of behavioral tests. Following electrical stimulation proximal to the hemitransection, lithium chloride at 0.2 mmol/kg decreased the latency and increased the amplitude of EMG responses in the denervated hindlimb at 56 dpi. Functional recovery was associated with reduced gray and white matter atrophy rostral and caudal to the hemitransection, increased neuronal survival and reduced astrogliosis in the dorsal and ventral horns caudal to the hemitransection, and increased regeneration of long-distance axons proximal and distal to the lesion site in mice receiving 0.2 mmol/kg, but not 2 mmol/kg lithium chloride, as assessed by histochemical and immunohistochemical studies combined with anterograde tract tracing. Our results indicate that lithium chloride induces long-term neurological recovery and neuroplasticity following spinal cord injury.